Ternary composite heterogeneous Fenton-like catalyst as well as preparation method and application thereof
By using MIL-88A/WS2 and CuFe2O4 for hydrothermal reaction in heterogeneous Fenton technology, the ternary composite heterogeneous Fenton catalyst formed by hydrothermal reactions has solved the problems of narrow pH range, difficulty in catalyst recovery, and poor stability in phenolic wastewater treatment, and significantly improved the treatment efficiency.
Patent Information
- Application Number
- CN202510077057.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing heterogeneous Fenton technology has problems such as narrow pH range, difficulty in recycling catalysts, poor stability, low PMS utilization rate and low degradation efficiency when treating phenolic wastewater.
By conducting hydrothermal reactions between MIL-88A/WS2 and CuFe2O4, a ternary composite heterogeneous Fenton catalyst was formed, and WS2 and CuFe2O4 were dispersed using MIL-88A as a support, and a circulation channel with tungsten ions, iron ions and copper ions was constructed.
The treatment efficiency of phenolic wastewater has been significantly improved, and the problems of weak electron conduction ability, limited pH adaptability and easy agglomeration of CuFe2O4 are overcome. It also solves the problems of poor catalyst stability, difficulty in recycling, low PMS utilization rate and low degradation efficiency.
Smart Images

Figure CN119746941A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a ternary composite heterogeneous Fenton-like catalyst and a preparation method and application thereof. Background Art
[0002] In recent years, the technology for treating phenolic wastewater has continued to become a research focus in the field of environmental protection. Although traditional methods, such as physical methods such as adsorption, membrane separation, coagulation and extraction, have significant effects in deep treatment, their treatment capacity is limited and they are not suitable for treating high-concentration and large-scale wastewater. Therefore, they need to be used in combination with other technologies. Although the oxidation and electrolysis technologies in chemical methods have high treatment efficiency, their reagents and equipment are expensive. Biological methods are limited in the treatment of wastewater by the difficulty of biodegradability, have long treatment cycles, low mineralization rates of pollutants, and sometimes even cause secondary pollution.
[0003] Heterogeneous Fenton technology, as a kind of advanced oxidation technology, has improved on the traditional Fenton technology. Due to its high treatment efficiency, relatively low cost and convenience of industrial application, it is gradually becoming one of the main methods in the field of deep wastewater treatment. In recent years, many foreign scholars have shifted the research focus of heterogeneous Fenton technology from the laboratory to engineering application, and are committed to solving the problem of treating practical difficult-to-degrade organic wastewater. At present, the research on heterogeneous Fenton technology mainly focuses on the preparation of heterogeneous catalysts and the transformation of reaction systems. The research focus of heterogeneous catalysts is mainly on the preparation of catalysts containing transition metal ions, and the research focus of the transformation of reaction systems is mainly on the transformation of oxidants and the change of reaction conditions (such as the introduction of electricity and light). The above studies have solved the problems existing in the homogeneous Fenton system to varying degrees and have practical research significance.
[0004] However, in practical applications, the heterogeneous Fenton process based on peroxymonosulfate (PMS) still faces many challenges, including: (1) a narrow applicable pH range; (2) the catalyst cannot be recycled; (3) the catalyst structure collapses, resulting in poor stability; (4) the utilization rate of PMS is not high; (5) Fe 2+ Activated SO4 2- Generates sulfate free radicals (SO4 ·- ) has a lower rate, while Fe 3+ with Fe 2+ The conversion efficiency between them is not ideal; (6) the catalyst is difficult to be effectively recycled after the reaction, which is not conducive to environmental protection. Therefore, there is an urgent need to improve the materials in the heterogeneous Fenton technology to reduce the adverse effects during the reaction and promote the application of the Fenton reaction in a wider range of fields.
[0005] Spinel ferrites are widely used in catalytic oxidation due to their useful magnetically recyclable properties, excellent catalytic performance, high stability, low toxicity and low ion leaching rate. Copper ferrite (CuFe2O4) is a typical spinel material, due to its high electron mobility and effective band gap of 1.6eV, but single CuFe2O4 has slightly inferior electron conductivity compared to other precious metals, limited pH adaptability, and agglomeration phenomenon that hinders its ability to degrade pollutants. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a ternary composite heterogeneous Fenton-like catalyst and a preparation method and application thereof. The present invention performs a hydrothermal reaction on MIL-88A / WS2 and CuFe2O4 to obtain a ternary composite heterogeneous Fenton-like catalyst. The present invention uses MIL-88A (Fe) as a carrier to effectively disperse WS2 and CuFe2O4, and constructs a circulation channel with tungsten ions, iron ions and copper ions between the three, so that the prepared ternary composite heterogeneous Fenton-like catalyst not only successfully overcomes the defects of weak electronic conductivity, limited pH adaptability and easy agglomeration of CuFe2O4, but also solves the problems of poor catalyst stability, difficulty in recycling, low PMS utilization rate and low degradation efficiency in heterogeneous Fenton-like technology, thereby significantly improving the treatment efficiency of phenol wastewater.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] The object of the present invention is to provide a method for preparing a ternary composite heterogeneous Fenton-like catalyst, comprising the following steps:
[0009] MIL-88A / WS2, CuFe2O4, ethylene glycol and water are mixed and subjected to a hydrothermal reaction. During the hydrothermal reaction II, CuFe2O4 is loaded on MIL-88A / WS2 to form a chemical bond, and a circulation channel with copper ions, iron ions and tungsten ions is constructed to obtain a ternary composite heterogeneous Fenton-like catalyst, wherein the mass ratio of MIL-88A / WS2, CuFe2O4, ethylene glycol and water is 2:1 to 8:5:1.
[0010] Preferably, in the preparation of the ternary composite heterogeneous Fenton-type catalyst, the conditions of the hydrothermal reaction are: reacting at 110° C. to 120° C. for 11 h to 12 h.
[0011] Preferably, CuFe2O4 is prepared according to the following steps:
[0012] NaOH solution is added dropwise to a mixed solution of Cu(NO3)2·3H2O, Fe(NO3)3·9H2O and water, and a coprecipitation reaction is carried out at 85°C to 90°C for 1.5h to 2h, followed by calcination to obtain CuFe2O4; wherein the molar ratio of Cu(NO3)2·3H2O, Fe(NO3)3·9H2O and NaOH is 2.5-3:5-6:300-400.
[0013] Preferably, the preparation steps of MIL-88A / WS2 are:
[0014] WS2, MIL-88A(Fe), ethylene glycol and water are mixed and subjected to a hydrothermal reaction to obtain MIL-88A / WS2, and MIL-88A / WS2 has a hollow structure; wherein the mass ratio of WS2 to MIL-88A(Fe) is 2:1; when the mass ratio of WS2 to MIL-88A(Fe) is 2:1, the degradation effect of the ternary composite heterogeneous Fenton-like catalyst is optimal; when the present invention uses MIL-88A / WS2, CuFe2O4, ethylene glycol and water as raw materials to prepare the ternary composite heterogeneous Fenton-like catalyst, the hollow structure of MIL-88A / WS2 will not be destroyed due to the selection of the solvent.
[0015] Preferably, in the preparation of MIL-88A / WS2, the hydrothermal reaction conditions are: reacting at 110° C. to 120° C. for 11 h to 12 h.
[0016] Preferably, the preparation method of MIL-88A(Fe) is:
[0017] FeCl3·6H2O, C4H4O4 and water are mixed and subjected to hydrothermal reaction at 80℃~100℃ for 11h~12h to obtain MIL-88A(Fe); wherein the molar ratio of FeCl3·6H2O to C4H4O4 is 1:1; MIL-88A is composed of organic ligands and metal ions. From the crystal structure and chemical composition of MIL-88A, its ideal structure is that iron ions and fumaric acid ligands are coordinated and assembled according to the stoichiometric ratio of 1:1; this molar ratio can ensure that each iron ion has a corresponding organic ligand C4H4O4 to coordinate, thereby constructing a complete MIL-88A(Fe); if it is higher or lower than this ratio, some iron ions will not be able to fully coordinate with the organic ligand C4H4O4, and other impurity phases or unreacted iron ions will be formed, affecting the purity and performance of MIL-88A(Fe).
[0018] Preferably, the preparation method of WS2 is:
[0019] After WCl6, thioacetamide and ethanol are mixed, a hydrothermal reaction is carried out at 190℃~200℃ for 23h~24h to obtain WS2; wherein the molar ratio of WCl6 to thioacetamide is 1:6~15; within this range, a process of gradual saturation of the nanosheet material can be seen.
[0020] The second object of the present invention is to provide a ternary composite heterogeneous Fenton-like catalyst prepared by the above preparation method.
[0021] Preferably, in the ternary composite heterogeneous Fenton-like catalyst, WS2 is coated on the spindle-rod-shaped MIL-88A in a nanosheet structure, and spherical CuFe2O4 is loaded on the nanosheet.
[0022] The third object of the present invention is to provide the use of the above-mentioned ternary composite heterogeneous Fenton-like catalyst in the preparation of a phenol wastewater treatment agent.
[0023] Preferably, the application method is:
[0024] The ternary composite heterogeneous Fenton-like catalyst is mixed with a phenol solution, and peroxymonosulfate is added under light-proof conditions. After stirring for reaction, a quencher is added to terminate the reaction; the mass volume ratio of the ternary composite heterogeneous Fenton-like catalyst, peroxymonosulfate and phenol solution is 0.06g-0.1g:0.1228g:200mL.
[0025] Preferably, the mass concentration of the phenol solution is 20 mg / L to 25 mg / L.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention provides a method for preparing a ternary composite heterogeneous Fenton-like catalyst. MIL-88A / WS2, CuFe2O4, ethylene glycol and water are mixed and subjected to a hydrothermal reaction. During the hydrothermal reaction, CuFe2O4 is loaded on MIL-88A / WS2. The sulfur atoms, unsaturated Fe and metal ions of CuFe2O4 on the surface of MIL-88A / WS2 interact with each other to form chemical bonds. The interface resistance is reduced through the interaction of chemical bonds (covalent bonds, ionic bonds), van der Waals forces and hydrogen bonds, so that MIL-88A, WS2 and CuFe2O4 are closely connected, and a circulation channel with copper ions, iron ions and tungsten ions is constructed, which significantly improves the electron transfer efficiency, and obtains a ternary composite heterogeneous Fenton-like catalyst. The mass ratio of MIL-88A / WS2, CuFe2O4, ethylene glycol and water is 2:1 to 8:5:1. The ternary composite heterogeneous Fenton-like catalyst prepared by the present invention has a heterojunction structure between MIL-88A / WS2 and CuFe2O4, which not only successfully overcomes the defects of CuFe2O4 such as weak electron conductivity, limited pH adaptability and easy agglomeration, but also solves the problems of poor catalyst stability, difficulty in recycling, low PMS utilization rate and low degradation efficiency in heterogeneous Fenton-like technology, thereby significantly improving the treatment efficiency of phenol wastewater.
[0028] Among them, ethylene glycol and water are used as solvents. Ethylene glycol has a higher viscosity. As a dispersant, it can promote the uniform dispersion of CuFe2O4 by forming weak interactions such as hydrogen bonds and van der Waals forces with the surfaces of MIL-88A / WS2 and CuFe2O4, adjust the viscosity and diffusion rate of the reaction system, and prevent agglomeration. When ethylene glycol is added, it helps to maintain the stability of the system for a long time and prevent MIL-88A / WS2 and CuFe2O4 from aggregating and precipitating after collision due to Brownian motion. The addition of water can adjust the overall polarity and viscosity of the system. Water can fine-tune the viscosity of the reaction system, making it conducive to the full mixing of MIL-88A / WS2 and CuFe2O4, and will not hinder the mutual collision between the ternary composite heterogeneous Fenton-like catalysts due to excessive viscosity.
[0029] 2. The ternary composite heterogeneous Fenton-like catalyst of the present invention has unique trimetallic active sites and multi-element structures, integrating the high porosity characteristics of MIL-88A metal-organic framework materials (MOFs) and their rich metal sites as active sites, the catalytic active sites at the edges and surfaces of WS2 layered materials, and the active sites inherent in the CuFe2O4 crystal structure. The composite of MIL-88A / WS2 and CuFe2O4 not only significantly enhances the number of active sites of the ternary composite heterogeneous Fenton-like catalyst, producing a significant synergistic effect, but also enables the ternary composite heterogeneous Fenton-like catalyst to act on the oxidant together. This multi-element composite structure can provide multiple ways to activate the oxidant, such as by changing the adsorption mode and electron transfer pathway of the oxidant, reducing the ineffective decomposition of the oxidant, and increasing the proportion of its conversion into hydroxyl radicals, thereby enhancing the ability to degrade pollutants, reducing treatment costs, and reducing secondary pollution caused by residual undecomposed oxidants.
[0030] 3. The present invention also applies the ternary composite heterogeneous Fenton-like catalyst to sewage treatment, which has the advantages of fast reaction rate, good degradation effect, wide reaction pH range, good stability and strong recovery performance.
[0031] In terms of reaction rate and degradation effect, the ternary composite heterogeneous Fenton-like catalyst of the present invention can have better tolerance to various interfering components in complex wastewater. Specifically, MIL-88A can remove some impurities in wastewater by adsorption, and WS2 and CuFe2O4 can maintain catalytic activity in complex chemical environments, thereby improving the pollutant removal effect in actual wastewater treatment.
[0032] In terms of stability and pH range, the framework structure of MIL-88A(Fe) can physically support WS2 and CuFe2O4, maintain the structural integrity of the ternary composite heterogeneous Fenton-like catalyst, and enable it to maintain a stable physical form during the reaction. At the same time, the magnetic properties of CuFe2O4 can play a dispersing role and prevent WS2 from agglomerating. The multi-component structure of the ternary composite heterogeneous Fenton-like catalyst also increases its ability to resist chemical changes. Under different pH values and redox environments, MIL-88A / WS2 and CuFe2O4 can cooperate with each other to reduce their own chemical changes, thereby extending the service life of the ternary composite heterogeneous Fenton-like catalyst.
[0033] In terms of recyclability, it is relatively difficult to recycle ordinary heterogeneous Fenton-like catalysts, but CuFe2O4 has magnetic properties, which enables the ternary composite heterogeneous Fenton-like catalyst to be quickly and efficiently recycled through an external magnetic field. This magnetic recyclability not only facilitates the reuse of the ternary composite heterogeneous Fenton-like catalyst and reduces costs, but also effectively prevents the catalyst from being lost to the environment, reducing the possibility of secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 These are the SEM images and TEM images of MIL-88A(Fe), WS2, MW, CuFe2O4 and MWC-0.1 prepared in Example 1, wherein (a) is the SEM image of MIL-88A(Fe), (b) is the SEM image of WS2, (c) is the SEM image of MW, (d) is the SEM image of CuFe2O4, (e) is the SEM image of MWC-0.1, and (f) is the TEM image of MWC-0.1 prepared in Example 1.
[0035] Figure 2 These are the XPS analysis results of MWC-0.1 prepared in Example 1, where (a) is the full spectrum, (b) is the O1s spectrum, (c) is the Fe2p spectrum, (d) is the W4f spectrum, (e) is the Cu2p spectrum, and (f) is the S2p spectrum.
[0036] Figure 3 The BET analysis results of CuFe2O4, MW and MWC-0.1 prepared in Example 1 are shown in Figure 1, where a is the N2 adsorption-desorption curve and b is the pore size distribution diagram.
[0037] Figure 4 These are the impedance spectra of CuFe2O4, MW and MWC-0.1 prepared in Example 1.
[0038] Figure 5 These are diagrams showing the effects of WS2, MW, and MWC-0.1 prepared in Example 1 on the degradation of pollutants in different systems.
[0039] Figure 6 This is a degradation curve of MWC-0.1 prepared in Example 1 at different initial pH values.
[0040] Figure 7 This is the cyclic stability diagram of MWC-0.1 prepared in Example 1.
[0041] Figure 8 This is the XRD diagram of MWC-0.1 prepared in Example 1 before and after the degradation of phenol in a Fenton-like system.
[0042] Fig. 9 VSM diagrams of CuFe2O4 and MWC-0.1 prepared in Example 1, wherein a is the vibrating sample magnetometer curve and b is the magnetic recovery catalyst diagram.
[0043] Fig.10 These are the EPR electron paramagnetic resonance images of WS2, MW, and MWC-0.1 obtained in Example 1. DETAILED DESCRIPTION
[0044] The technical solution of the present invention will be clearly and completely described below in combination with the data in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0046] In the existing technology, heterogeneous Fenton-like technology, as an advanced oxidation technology, has the advantages of high treatment efficiency and relatively low cost, but it still faces many difficulties in practical application, such as narrow applicable pH range, difficulty in recycling and reusing catalysts, poor stability, low utilization rate of peroxymonosulfate (PMS) and Fe 2+ Activated SO4 2- Generates sulfate free radicals (SO4 ·- ) rate and Fe 3+ with Fe 2+ Although CuFe2O4 has catalytic properties, it has problems such as weak electron conductivity, limited pH adaptability and easy agglomeration, which limits its application in wastewater treatment.
[0047] In view of the problems existing in the prior art, the present invention proposes a preparation method of a ternary composite heterogeneous Fenton-like catalyst, comprising the following steps: mixing MIL-88A / WS2, CuFe2O4, ethylene glycol and water, and performing a hydrothermal reaction, during which CuFe2O4 is loaded on MIL-88A / WS2 and interacts with sulfur atoms on the surface of WS2 and metal sites in MIL-88A to form new chemical bonds, thereby constructing a circulation channel with copper ions, iron ions and tungsten ions, and obtaining a MIL-88A / WS2 / CuFe2O4 ternary composite heterogeneous Fenton-like catalyst, wherein the mass ratio of MIL-88A / WS2, CuFe2O4, ethylene glycol and water is 2:1 to 8:5:1.
[0048] The ternary composite heterogeneous Fenton-like catalyst prepared by the present invention not only overcomes the defects of CuFe2O4 such as weak electron conductivity, limited pH adaptability and easy agglomeration, but also solves the problems of poor catalyst stability, difficulty in recycling, low PMS utilization rate and low degradation efficiency in heterogeneous Fenton-like technology.
[0049] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0050] Example 1
[0051] A method for preparing a ternary composite heterogeneous Fenton-like catalyst specifically comprises the following steps:
[0052] S1. Preparation of MIL-88A (Fe):
[0053] 10 mmol of FeCl3·6H2O (2.703 g) and 10 mmol of C4H4O4 (1.1607 g) were placed in a beaker containing 50 mL of deionized water and stirred continuously for 15 min. Then, they were placed in a 150 mL Teflon-lined stainless steel autoclave. Next, they were heated in a 100°C forced air drying oven for 12 h. After the reaction was completed, they were naturally cooled to room temperature. The orange-brown product was centrifuged at 8000 r / min for 8 min. Finally, it was washed alternately with deionized water and anhydrous ethanol and dried in vacuum at 60°C for 12 h to obtain MIL-88A (Fe).
[0054] Preparation of S2 and WS2:
[0055] Weigh one of WCl6 (0.9914 g, 2.5 mmol) and thioacetamide (2.2539 g, 30 mmol), add it into a beaker containing 60 mL of anhydrous ethanol, and stir for 30 min to mix it evenly. Then heat it in a 100 ml Teflon-lined hydrothermal reactor at 200 ° C for 24 h. After the reactor is naturally cooled to room temperature, collect the black product produced in the reaction system and wash it alternately with deionized water and anhydrous ethanol for 6 times. Finally, dry it at 70 ° C in a vacuum drying oven for 12 h to obtain WS2.
[0056] Preparation of S3 and CuFe2O4:
[0057] CuFe2O4 was prepared by coprecipitation method. First, 0.025 mol of Cu(NO3)2·3H2O (6.04 g) and 0.05 mol of Fe(NO3)3·9H2O (20.20 g) were added to a beaker containing 100 mL of deionized water, stirred for 30 min, and then transferred to a three-necked flask. Then 75 mL of 4.0 mol of NaOH solution was added dropwise while stirring, and heated at 90°C for 2 h. After cooling to room temperature, washing, drying, and then heating to 600°C at a rate of 2°C / min in a test tube and keeping warm for 2 h, CuFe2O4 was obtained.
[0058] Preparation of S4, MIL-88A / WS2:
[0059] 0.2 g of WS2 and 0.1 g of MIL-88A(Fe) were mixed in a mixed solution of 25 mL of ethylene glycol and 5 mL of deionized water. After ultrasonic treatment for 30 min, the mixture was placed in a 50 mL eflon-lined hydrothermal reactor and heated at 120 °C for 12 h. The mixture was washed and dried to obtain MIL-88A / WS2, recorded as MW.
[0060] S5. Preparation of MIL-88A / WS2 / CuFe2O4 ternary composite heterogeneous Fenton-like catalyst:
[0061] CuFe2O4 was composited on the basis of MIL-88A / WS2. 0.2g of MIL-88A / WS2 and 0.1g of CuFe2O4 were mixed in a mixed solution of 25mL of ethylene glycol and 5mL of deionized water. After ultrasonic treatment for 30min, the mixture was placed in a 50mL Teflon-lined hydrothermal reactor and heated at 120°C for 12h. The mixture was washed and dried to obtain MIL-88A / WS2 / CuFe2O4, i.e., a ternary composite heterogeneous Fenton-like catalyst, recorded as MWC-0.1.
[0062] Example 2
[0063] A method for preparing a ternary composite heterogeneous Fenton-like catalyst is the same as the preparation method of Example 1, except that the amount of CuFe2O4 in S5 is replaced from 0.1g to 0.2g to obtain MIL-88A / WS2 / CuFe2O4, i.e., a ternary composite heterogeneous Fenton-like catalyst, recorded as MWC-0.2.
[0064] Example 3
[0065] A method for preparing a ternary composite heterogeneous Fenton-like catalyst is the same as the preparation method of Example 1, except that the amount of CuFe2O4 in S5 is replaced from 0.1g to 0.4g to obtain MIL-88A / WS2 / CuFe2O4, i.e., a ternary composite heterogeneous Fenton-like catalyst, recorded as MWC-0.4.
[0066] Example 4
[0067] A method for preparing a ternary composite heterogeneous Fenton-like catalyst is the same as the preparation method of Example 1, except that the amount of CuFe2O4 in S5 is replaced from 0.1g to 0.6g to obtain MIL-88A / WS2 / CuFe2O4, i.e., a ternary composite heterogeneous Fenton-like catalyst, recorded as MWC-0.6.
[0068] Example 5
[0069] A method for preparing a ternary composite heterogeneous Fenton-like catalyst is the same as the preparation method of Example 1, except that the amount of CuFe2O4 in S5 is replaced from 0.1g to 0.8g to obtain MIL-88A / WS2 / CuFe2O4, i.e., a ternary composite heterogeneous Fenton-like catalyst, recorded as MWC-0.8.
[0070] The ternary composite heterogeneous Fenton-like catalysts prepared in Examples 1 to 5 of the present invention have basically the same morphology. The ternary composite heterogeneous Fenton-like catalyst prepared in Example 1 was subjected to an electron microscope scanning test, and the results were observed. Figure 1 It is concluded that Figure 1 In Figure a, a spindle-like structure appeared, indicating that MIL-88A was successfully prepared; Figure 1 Figure b shows a spherical structure of stacked nanosheets, and the nanosheets on the spherical surface are fully stacked, which indicates that WS2 was successfully prepared. Figure 1 Figure c shows that WS2 is loaded on MIL-88A in a nanoflower layered structure, and MIL-88A / WS2 is successfully prepared; Figure 1 Figure d shows the spherical structure of CuFe2O4, and CuFe2O4 was successfully prepared; Figure 1 Figure e shows that WS2 is loaded on MIL-88A in a nanoflower layered structure, and the nanosheet layer continues to load the CuFe2O4 spherical structure, and the MIL-88A / WS2 / CuFe2O4 ternary composite material is successfully prepared. In summary, Example 1 successfully prepared MIL-88A (Fe), WS2, CuFe2O4, MW and MWC-0.1, and they are evenly distributed on the spindle-shaped material MIL-88A (Fe).
[0071] Figure 2 (a) shows that C, O, S, Fe, W, and Cu elements exist in the ternary composite heterogeneous Fenton-like catalyst, indicating that the ternary composite heterogeneous Fenton-like catalyst was successfully prepared; Figure 2 (b) is the XPS spectrum of O1s, in which three obvious peaks belong to WO, Fe-O and -COOH, indicating that WS2 and MIL-88A(Fe) are preserved in MWC-0.1; Figure 2 (c) shows the XPS spectrum of Fe 2p. The peaks at 709.9 and 723.1 eV correspond to Fe 2+ 2p 3 / 2 and 2p 1 / 2 , the peaks at 713.3 and 726.8 eV correspond to Fe 3+ 2p 3 / 2 and 2p 1 / 2 , indicating that Fe exists in MW-0.1 2+ / Fe 3+,In addition, satellite peaks were found at 717.1 and 730.9 eV; Figure 2 (d) shows the XPS spectrum of W 4f, which belongs to W 4+ W 4f 5 / 2 and W 4f 7 / 2 After orbital splitting, the characteristic peaks at 32.0 eV and 34.1 eV are attributed to 1T-WS2, while the characteristic peak at 33.1 eV is attributed to 2H-WS2, which indicates that 1T-WS2 and 2H-WS2 coexist in MW-0.1, and 1T-WS2 is dominant; Figure 2 (e) is the XPS spectrum of Cu 2p, there are two main Cu 2p 3 / 2 peaks, with binding energies of 932.1eV and 952.1eV, respectively, belonging to Cu + and Cu 2+ , in Cu 2p 1 / 2 The peak can also be found in Cu + and Cu 2+ At the binding energy of 943.4 eV, a strong Cu 2+ Satellite Peak; Figure 2 (f) is the S2p spectrum, where S2p 3 / 2 (161.7 eV) and S2p 1 / 2 The binding energy of (163.0 eV) can be assigned to S 2- This indicates that sulfur species (referring to sulfide and sulfate) and Fe-S bonds exist on the surface of MWC-0.1. The peaks at 164.3 and 169.2 eV are unsaturated sulfur and sulfate (SOX), respectively. Based on the above results, the presence of Fe 3+ / Fe 2+ , Cu 2+ / Cu + , W 6+ / W 4+ , and multiple active sites of unsaturated S coexist. This proves that the 1T phase WS2 and the ternary composite heterogeneous Fenton-like catalyst were successfully prepared.
[0072] The following is an example of the MIL-88A / WS2 / CuFe2O4 ternary composite heterogeneous Fenton-like catalyst prepared in Example 1 of the present invention, which is applied to activate PMS to degrade phenol, and the degradation effect is explored. The specific application method is as follows:
[0073] The MWC-0.1 prepared in Example 1 was used to carry out a heterogeneous Fenton-like reaction, and the specific steps were as follows: MW-0.1 was added to a glass beaker containing 200 mL of a 20 mg / L phenol solution, and after reacting in the dark for 30 minutes to reach adsorption equilibrium, peroxymonosulfate was added to the above solution, and the mass ratio of MWC-0.1 to peroxymonosulfate was 0.06:0.1228, inducing a heterogeneous Fenton-like reaction. After the reaction lasted for 60 minutes, 4 mL of the suspension was extracted, and 0.2 mL of methanol was added as a quencher to terminate the reaction; then, after filtering with a 0.22 μm filter membrane, 2 mL of the supernatant was extracted for determination.
[0074] The determination method is: phenol is determined by tetraamine antipyrine spectrophotometry using a 722G visible light spectrophotometer at a wavelength of 510 nm.
[0075] observe Figure 3 It was concluded that the specific surface area of the ternary composite heterogeneous Fenton-like catalyst was improved and it was a typical mesoporous material. Figure 3 The isotherms of MW and MWC-0.1 in Figure a are consistent with the IV type isotherm, and the IV type isotherm of the H3 hysteresis loop is in a relatively high relative pressure range (P / P0=0.45-1.0), indicating that MW and MWC-0.1 are mesoporous structures. At the same time, it is proved that the ternary composite heterogeneous Fenton-like catalyst prepared by the present invention has IV type isotherm characteristics and a hysteresis loop. The specific surface areas of MWC-0.1, MW and CuFe2O4 are 24.1492m 2 / g, 15.3878m 2 / g and 17.0788m 2 / g; Figure 3 The pore size of the ternary composite material in Figure b is the largest. These results prove that due to the presence of CuFe2O4, the ternary composite heterogeneous Fenton-like catalyst MWC-0.1 can provide a larger contact area and channel for the interaction between the reaction active sites and the target pollutants compared to MW, thus having a higher catalytic activity.
[0076] The MW, CuFe2O4 and MWC-0.1 prepared in Example 1 were used as working electrodes, the Ag / AgCl electrode was used as the reference electrode, and the platinum electrode was used as the counter electrode. One end of the working electrode, the reference electrode and the counter electrode was placed in a 0.5 mol / L Na2SO4 solution, and the other ends were electrically connected to an electrochemical workstation (CHI660E) for electrochemical analysis at a scan rate of 5 mV / s. The test results are shown below:
[0077] Depend on Figure 4It was concluded that MWC-0.1 had the smallest arc radius among all ternary composite heterogeneous Fenton-like catalysts. EIS results showed that the formation of heterojunction in MWC-0.1 provided separation of carriers and slower recombination, thus improving the catalytic performance, compared with the use of MW and CuFe2O4 alone.
[0078] WS2, MIL-88A, MW, CuFe2O4 and MWC-0.1 were mixed with permonosulfate, and the obtained systems were recorded as WS2 / PMS, MIL-88A / PMS, MW / PMS, CuFe2O4 / PMS and MWC-0.1 / PMS, respectively; among which, the mass ratios of WS2, MIL-88A, MW, CuFe2O4 and MWC-0.1 to permonosulfate were all 0.06:0.1228.
[0079] a. PMS, MW / PMS, CuFe2O4 / PMS, MIL-88A / PMS, MWC-0.1 / PMS, WS2 / PMS or MWC-0.1 with a mass concentration of 0.3 g / L were stirred and mixed with a phenol solution with an initial mass concentration of 20 mg / L and a pH of 7.0 at room temperature to perform a degradation experiment and measure the mass concentration of the phenol solution in the system. The phenol volume, i.e., the total volume of the system, was always 200 mL.
[0080] b. The prepared MWC-0.1 was subjected to a phenol degradation cycle experiment, wherein the cycle method was as follows: washing the MWC-0.1 with deionized water and anhydrous ethanol alternately three times, and then drying the MWC-0.1 in a vacuum drying oven before use.
[0081] observe Figure 5 It was concluded that, except for MWC-0.1 / PMS and MW / PMS, which had strong degradation effects on phenol, the other systems could only degrade a small part of phenol through the self-decomposition of a small part of PMS, and the degradation efficiency of the MWC-0.1 / PMS system was greatly improved compared with that of the MW / PMS system.
[0082] observe Figure 6 It is concluded that the ternary composite heterogeneous Fenton-like catalyst of the present invention can maintain high catalytic activity within the initial pH value range of 3.0 to 9.0.
[0083] Depend on Figure 7 It was concluded that the ternary composite heterogeneous Fenton-like catalyst of the present invention can still maintain good stability after 5 cycle experiments.
[0084] observe Figure 8It was found that the position and intensity of the characteristic peak of MWC-0.1 showed almost no change before and after the degradation of phenol by the MWC-0.1 / PMS Fenton-like system, which indicates that the basic structure of MWC-0.1 was kept intact and stable during the reaction, indicating that the ternary composite heterogeneous Fenton-like catalyst of the present invention has excellent stability.
[0085] observe Fig. 9 Figure a shows that the saturation magnetization of the ternary composite heterogeneous Fenton-like catalyst is 26.87emu / g, indicating that it has very good magnetic properties. Fig. 9 Figure b shows that the ternary composite heterogeneous Fenton-like catalyst has good magnetic recovery ability.
[0086] observe Fig.10 It was found that with the increase of hydrothermal times, the S vacancy signal gradually increased, and the strongest S vacancy peak appeared at MWC-0.1, indicating the existence of S vacancies in the ternary composite heterogeneous Fenton-like catalyst.
[0087] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiment, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art can make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiment and all changes and modifications that fall within the scope of the present invention.
Claims
1. A method for preparing a ternary composite heterogeneous Fenton-like catalyst, characterized in that: The steps include: MIL-88A / WS2, CuFe2O4, ethylene glycol and water are mixed and subjected to a hydrothermal reaction. During the hydrothermal reaction, CuFe2O4 is loaded on MIL-88A / WS2 and interacts with sulfur atoms on the surface of WS2 and metal sites in MIL-88A to form new chemical bonds, thereby obtaining a MIL-88A / WS2 / CuFe2O4 ternary composite heterogeneous Fenton-like catalyst. Among them, the mass ratio of MIL-88A / WS2, CuFe2O4, ethylene glycol and water is 2:1 to 8:5:
1.
2. The method for preparing the ternary composite heterogeneous Fenton-like catalyst according to claim 1, characterized in that: The conditions of the hydrothermal reaction are: react at 110°C to 120°C for 11h to 12h.
3. The method for preparing the ternary composite heterogeneous Fenton-like catalyst according to claim 1, characterized in that: CuFe2O4 was prepared according to the following steps: The NaOH solution is added dropwise to a mixed solution of Cu(NO3)2·3H2O, Fe(NO3)3·9H2O and water, and a coprecipitation reaction is carried out at 85°C to 90°C for 1.5h to 2h, followed by calcination to obtain CuFe2O4; Among them, the molar ratio of Cu(NO3)2·3H2O, Fe(NO3)3·9H2O and NaOH is 2.5~3:5~6:300~400.
4. The method for preparing the ternary composite heterogeneous Fenton-like catalyst according to claim 1, characterized in that: MIL-88A / WS2 is prepared as follows: WS2, MIL-88A(Fe), ethylene glycol and water are mixed and subjected to a hydrothermal reaction to obtain MIL-88A / WS2; Among them, the mass ratio of WS2 to MIL-88A(Fe) is 2:
1.
5. The method for preparing the ternary composite heterogeneous Fenton-like catalyst according to claim 4, characterized in that: The conditions of the hydrothermal reaction are: react at 110°C to 120°C for 11h to 12h.
6. A ternary composite heterogeneous Fenton-like catalyst prepared by the preparation method according to any one of claims 1 to 5.
7. The ternary composite heterogeneous Fenton-like catalyst according to claim 6, characterized in that: In the ternary composite heterogeneous Fenton-like catalyst, WS2 is coated on the spindle-shaped MIL-88A in a nanosheet structure, and spherical CuFe2O4 is loaded on the nanosheet.
8. Use of the ternary composite heterogeneous Fenton-like catalyst according to claim 6 in preparing a phenol wastewater treatment agent.
9. Use of the ternary composite heterogeneous Fenton-like catalyst according to claim 8 in preparing a phenol wastewater treatment agent, characterized in that: The application method is: The ternary composite heterogeneous Fenton-like catalyst is mixed with a phenol solution, and peroxymonosulfate is added under light-proof conditions, and after stirring for reaction, a quencher is added to terminate the reaction; The mass volume ratio of the ternary composite heterogeneous Fenton-like catalyst, peroxymonosulfate and phenol solution is 0.06g-0.1g:0.1228g:200mL.
10. Use of the ternary composite heterogeneous Fenton-like catalyst according to claim 9 in preparing a phenol wastewater treatment agent, characterized in that: The mass concentration of the phenol solution is 20 mg / L to 25 mg / L.
Citation Information
Patent Citations
Copper ferrite-metal organic framework structure composite material as well as preparation method and application thereof
CN112452301A
Silver-copper ferrite-iron-based metal organic framework composite material as well as preparation method and application thereof
CN116870969A
Tungsten sulfide modified iron-based MOF (Metal Organic Framework) water treatment photo-Fenton catalyst as well as preparation method and application thereof
CN117732507A
MIL-88A-WS2 composite material as well as preparation method and application thereof
CN119456036A
Image processing network module, image processing device and method of operation of the image processing device
KR1020250094508A